2018
DOI: 10.24926/iip.v9i3.1392
|View full text |Cite
|
Sign up to set email alerts
|

Laptop Versus Longhand Note Taking in a Professional Doctorate Course: Student Performance, Attitudes, and Behaviors

Abstract: Objective: To determine the relationship between longhand note taking versus laptop note taking on pharmacy students’ examination performance and identify differences in attitudes and behaviors as it relates to the note taking process. Methods: A small group of students consented voluntarily to take longhand notes, doing away with their laptops during portions of the course administered by study investigators. Analyses were conducted on block examination performance, with each student’s score on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…[6][7][8][9][10][11] At the graduate level of learning, several authors suggested that handwritten note-taking is superior to learning outcomes, although not always significant in difference. 2,19 With our findings focusing on graduate physical therapy students, we found that handwritten note-takers tended toward having higher course grades, but they did not significantly outperform the digital note-taking group.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…[6][7][8][9][10][11] At the graduate level of learning, several authors suggested that handwritten note-taking is superior to learning outcomes, although not always significant in difference. 2,19 With our findings focusing on graduate physical therapy students, we found that handwritten note-takers tended toward having higher course grades, but they did not significantly outperform the digital note-taking group.…”
Section: Discussionmentioning
confidence: 70%
“…Results indicated that although the longhand note-taking group performed better than the digital note-takers on the 2 remaining examinations, the results were not significant. 2 Individual Differences and Note-taking No studies exist that specifically explore notetaking method and student individual differences among graduate students. However, studies do exist that focus on student differences.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Rather than using an experimental set-up, as in the above three studies, Desselle and Shane (2018) studied longhand and laptop note-taking on pharmacy students' performance during two exams in a professional doctorate course. They found a 3.5% improvement in examination scores for longhand note-taking students.…”
Section: Introductionmentioning
confidence: 99%